The Contribution of Arm Muscle Strength to Badminton Smash Accuracy among Students - Gilang Kurniawan; Yanuar Kiram; Yendrizal; Eval Edmizal (Jurnal Master Penjas & Olahraga, 2026)
This study aimed to determine the contribution of arm muscle strength to badminton smash accuracy among students participating in the badminton extracurricular program at SMAN 1 Lintau Buo. A quantitative correlational design was employed involving 10 students selected through total sampling. Arm muscle strength was measured using a 60-second push-up test, while smash accuracy was assessed using a badminton smash accuracy test. Data were analyzed using descriptive statistics, Pearson Product-Moment correlation, and the coefficient of determination at a significance level of 0.05. The results showed no significant relationship between arm muscle strength and smash accuracy (r = 0.058, p = 0.874), with a contribution of only 0.34%. These findings suggest that smash accuracy is influenced more by technical proficiency, coordination, movement timing, and biomechanical factors than by arm muscle strength alone. Therefore, integrated training programs are recommended to improve badminton smash performance.